Differential Associations between Ovarian Hormones and Disordered Eating Symptoms across the Menstrual Cycle in Women - Racine, Sarah E. (2011)
OBJECTIVE: We examined changes in drive for thinness, body dissatisfaction, and dietary restraint across the menstrual cycle and associations between these symptoms and ovarian hormones in two independent samples of women (N = 10 and 8 women, respectively) drawn from the community. METHOD: Daily self-report measures of disordered eating and negative affect were completed for 35–65 days. Daily saliva samples were assayed for estradiol and progesterone in Study 2 only. RESULTS: Levels of body dissatisfaction and drive for thinness were highest during the mid-luteal/pre-menstrual phases in both studies and were negatively associated with estradiol, and positively associated with progesterone. By contrast, dietary restraint showed less variation across the menstrual cycle and weaker associations with ovarian hormones. DISCUSSION: Differential associations between ovarian hormones and specific disordered eating symptoms point to distinct etiological processes within the broader construct of disordered eating.